Introduction to Petrology - Johnson, Elizabeth; Liu, Juhong Christie (Open textbook library., 2021)
Learn about igneous and metamorphic rocks (and how to analyze them), the fun way! Students learn concepts and practice knowledge by conducting inquiries guided with examples based on videos and interactive diagrams.